Answer:
c. Moon A is four times as massive as moon B
Step-by-step explanation:
Let's assume the:
- mass of the object =
- mass of the moon A =
- mass of the moon B =
- distance between the center of masses of the object and moon B =
According to the given condition the object is twice as far from moon A as it is from moon B
- ∴distance between the center of masses of the object and moon B =
As we know, gravitational force of attraction is given by:
According to the condition
Force on m due to
Force on m due to